Comparative study on risk factors and early outcome of symptomatic distal versus proximal deep vein thrombosis: results from the OPTIMEV study - Galanaud, Jean-Philippe; Sevestre-Pietri, Marie-Antoinette; Bosson, Jean-Luc; Laroche, Jean-Pieere; Righini, Marc; Brisot, Dominique; Boge, Gudrun; van Kien, Aaurelie Khau; Gattolliat, Olivier; Bettarel-Binon, Catherine; Gris, Jean-Christophe; Genty, Celine; et al. (Thrombosis and haemostasis, 2009)
There is a lack of consensus on the value of detecting and treating symptomatic isolated distal deep-vein thrombosis (DVT) of the lower limbs. In our study, we compared the risk factors and outcomes in patients with isolated symptomatic distal DVT with those with proximal symptomatic DVT. We analysed the data of patients with objectively confirmed symptomatic isolated DVT enrolled in the national (France), multicenter, prospective OPTIMEV study. This sub-study outcomes were recurrent venous thromboembolism, major bleeding and death at three months. Among the 6141 patients with suspicion of isolated DVT included between November 2004 and January 2006, DVT was confirmed in 1643 patients (26.8%). Isolated distal DVT was more frequent than proximal DVT (56.8% vs. 43.2%, respectively; p = 0.01). Isolated distal DVT was significantly more often associated with transient risk factors (recent surgery, recent plaster immobilisation, recent travel), whereas proximal DVT was significantly more associated with more chronic states (active cancer, congestive heart failure or respiratory insufficiency, age >75 years). Most patients (96.8%) with isolated distal DVT received anticoagulant therapies. There was no difference in the percentage of recurrent venous thromboembolism and major bleeding in patients with proximal DVT and isolated distal DVT. However, the mortality rate was significantly higher (p < 0.01) in patients with proximal DVT (8.0%) than in those with isolated distal DVT (4.4%). Symptomatic isolated distal DVT differs from symptomatic proximal DVT both in terms of risk factors and clinical outcome. Whether these differences should influence the clinical management of these two events remains to be determined.